Autophagy determines efficiency of liver‐directed gene therapy with adeno‐associated viral vectors. Issue 1 (29th May 2017) - Hösel, Marianna; Huber, Anke; Bohlen, Susanne; Lucifora, Julie; Ronzitti, Giuseppe; Puzzo, Francesco; Boisgerault, Florence; Hacker, Ulrich T.; Kwanten, Wilhelmus J.; Klöting, Nora; Blüher, Matthias; Gluschko, Alexander; et al.
Abstract : Use of adeno‐associated viral (AAV) vectors for liver‐directed gene therapy has shown considerable success, particularly in patients with severe hemophilia B. However, the high vector doses required to reach therapeutic levels of transgene expression caused liver inflammation in some patients that selectively destroyed transduced hepatocytes. We hypothesized that such detrimental immune responses can be avoided by enhancing the efficacy of AAV vectors in hepatocytes. Because autophagy is a key liver response to environmental stresses, we characterized the impact of hepatic autophagy on AAV infection. We found that AAV induced mammalian target of rapamycin (mTOR)–dependent autophagy in human hepatocytes. This cell response was critically required for efficient transduction because under conditions of impaired autophagy (pharmacological inhibition, small interfering RNA knockdown of autophagic proteins, or suppression by food intake), recombinant AAV‐mediated transgene expression was markedly reduced, both in vitro and in vivo . Taking advantage of this dependence, we employed pharmacological inducers of autophagy to increase the level of autophagy. This resulted in greatly improved transduction efficiency of AAV vectors in human and mouse hepatocytes independent of the transgene, driving promoter, or AAV serotype and was subsequently confirmed in vivo . Specifically, short‐term treatment with a single dose of torin 1 significantly increased vector‐mediated hepatic expression of erythropoietin in C57BL/6 mice. Similarly, coadministration of rapamycin with AAV vectors resulted in markedly enhanced expression of human acid‐α‐glucosidase in nonhuman primates. Conclusion : We identified autophagy as a pivotal cell response determining the efficiency of AAVs intracellular processing in hepatocytes and thus the outcome of liver‐directed gene therapy using AAV vectors and showed in a proof‐of‐principle study how this virus–host interaction can be employed to enhance efficacy of this vector system. (Hepatology 2017;66:252–265).